2020
DOI: 10.1021/acs.energyfuels.9b03883
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study on the Suitable Compatibility Conditions of a CO2-Cosolvent-Light Hydrocarbon System by Calculating the Solubility Parameters

Abstract: Molecular dynamics simulations were performed to calculate the solubility parameters of oil molecules (such as straight-chain alkanes, cycloalkanes, and aromatics) and CO2 + cosolvent systems. It was found that the solubility parameter of supercritical carbon dioxide (SC-CO2) increases with the increase of pressure at a fixed temperature, decreases with the increase of temperature at a fixed pressure, and increases linearly with the increase of the SC-CO2 system density. The simulated results showed that the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Recent studies on the solubility of light hydrocarbons in CO 2 demonstrated notable improvements when cosolvent was added to the uid. 17,18 The current application requires that only small amounts of oxidizing salts be dissolved in CO 2 . For subterranean applications where oxidizers are utilized in aqueous uids, concentrations are typically in the range of a few pounds per thousand gallons of uid (<0.1 wt%).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the solubility of light hydrocarbons in CO 2 demonstrated notable improvements when cosolvent was added to the uid. 17,18 The current application requires that only small amounts of oxidizing salts be dissolved in CO 2 . For subterranean applications where oxidizers are utilized in aqueous uids, concentrations are typically in the range of a few pounds per thousand gallons of uid (<0.1 wt%).…”
Section: Introductionmentioning
confidence: 99%
“…Du et al. 27 and Zhang et al. 11 also used the COMPASS force field to predict the solubility parameter of SC‐CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The box was geometrically optimized to achieve the most stable amorphous cell. As a final point, in order to achieve equilibrium at the desired temperature, the NVT ensemble [10,11,39] was used for 100 ps with time steps of 1 fs [10,11,27]. Also, a Nose thermostat [10] was used to control the temperature.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations